PENGARUH HEALING GARDENS TERHADAP PENURUNAN KECEMASAN PASIEN DI SALAH SATU RUMAH SAKIT SWASTA YOGYAKARTA - Fransisca Anjar Rina Setyani; Siwi Ikaristi Maria Theresia (MEDIA ILMU KESEHATAN, 2019)
Background: Chronic disease often cause patients feeling anxious in which it give negative consequences on their physical, emotional, social, intelectual and spiritual condition. Nurse can applay complementary therapy such as healing gardens to reduce patient anxiety level. Healing gardens can give comfortable situation, therfore it can improve relaxtation and reduce stress that can make hospitalization shorter. Some researres, results show that healing gardens can improve relaxtation and reduce patients anxiety who are sick. Objective: To identify the relationship between healing gardens toward reducing chronic patients anxiety level in one of Private Hospital in Yogyakarta. Methods: Research design which was done was observation. Population in this research were all chronical hospitalized patient in in one of Private Hospital in Yogyakartaa from August to October 2015. Total sample in this research were 30 respondens who are choosed randomly. Results: The test result of data analysis on the difference of before and after experiencing healing gardens showed p value 0.000 (p value < 0.05), means that healing gardens can reduce chronical panients anxiety level. Conculsion: Healing gardens can reduce anxiety level in chronic illnes patients. Hospital should applay healing gardens toward chronical patients in order to reduce patient anxiety level.